Les décisions de l'Office de la langue française en vertu de l'article 46 de la « Charte de la langue française » - Prujiner, Alain (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1981)
The prohibition of an employer to require the knowledge of a language other than French as condition of employment, enacted by section 46 of the Charter of the French Language, can be dismissed when the nature of the duties requires the knowledge of another language. The burden of proof however is on the employer. Exceptionnally, the Charter has granted the Office de la langue française a quasi-judiciary power « to decide any dispute » concerning this requirement. This article deals with the first decisions pronounced which specify accessibility to the above procedure (Part one) and define criteria concerning the knowledge of another language (Part two).